Breastfeeding Interpersonal Communication and Mobile Phone Support by Private Health Care Providers in Lagos, Nigeria Increased Exclusive Breastfeeding at 6 and 24 Weeks. (7th June 2021) - Flax, Valerie; Ipadeola, Abiodun; Schnefke, Courtney; Ralph-Opara, Uche; Adeola, Olatoun; Edwards, Susan; Bose, Sujata; Brower, Alice
Abstract: Objectives: Interventions to improve breastfeeding practices have not been tested in private facilities in Nigeria, although most urban facilities are private. The objective of this study was to measure the impact of Alive & Thrive's intervention on breastfeeding intentions, early initiation of breastfeeding, and exclusive breastfeeding among clients of private facilities in Lagos, Nigeria. Methods: The intervention included breastfeeding interpersonal communication during facility visits, breastfeeding text/WhatsApp messages, WhatsApp support groups, and social behavior change communication materials. Logistic regression models adjusted for clustering were used to detect differences in a cohort of women (N = 1, 200) at 10 intervention and 10 comparison facilities interviewed during their third trimester and at 6 and 24 weeks postpartum. Results: During pregnancy, intention to exclusively breastfeed at 6 weeks postpartum was 92% in both study arms, but more women in the intervention than comparison arm intended to exclusively breastfeed at 24 weeks postpartum (78% intervention, 64% comparison, p < 0.001). Early initiation of breastfeeding did not differ by study arm (35% intervention, 33% comparison). More women in the intervention than comparison arm exclusively breastfed at 6 weeks (83% intervention, 76% comparison, p = 0.02) and 24 weeks postpartum (66% intervention, 52% comparison, p < 0.001). Among women exclusively breastfeeding at 6 weeks, the odds of continued exclusive breastfeeding at 24 weeks was higher in the intervention than comparison arm (OR 1.6, p = 0.005). Conclusions: A breastfeeding intervention implemented in private health facilities in Lagos increased exclusive breastfeeding intentions and practices. Widespread implementation of breastfeeding interventions in private facilities could extend the reach of breastfeeding promotion programs in urban Nigeria. Funding Sources: This research was funded by the Alive & Thrive initiative, managed by FHI Solutions, and currently funded by the Bill & Melinda Gates Foundation, Irish Aid, the Tanoto Foundation, UNICEF, and the World Bank.